STRATEGI PEDAGANG BUAH DALAM BERJUALAN DI PASAR PAGI ARENGKA KOTA PEKANBARU - Chika, Adila De; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The strategy of fruit traders in selling at the morning Market of Arengka, Pekanbaru City. This research was conducted at Arengka Market, Pekanbaru City. The purpose of this study was to determine the costs and rewards of fruit traders and the strategies of fruit traders in carrying out selling activities. In determining the informants using a purposive sampling technique, namely fruit traders who do not cooperate with fruit traders around the market, have been selling for more than five years, and persisted in selling when the flyover was established. The number of informants in this study were five people. The theory used is the theory of social exchange by George Casper Homans. The results obtained are that the costs made are sacrifices in the form of time, material (paying rent), and in their own way. Rewards obtained by informants are in the form of material (money, have assets, and are able to meet daily needs) and non-material (comfort, security, and pleasure). Of course, this is different for each informant. As for the strategy, it is seen through the propositions in social exchange theory and assisted by cost analysis, so that rewards are also obtained for each informant. In general, the strategy taken by each informant is in the form of improving service to buyers in the form of providing good quality fruit, being friendly to buyers, being honest with customers, and giving discounts to customers. To support this strategy so that it runs smoothly and according to its objectives, of course it requires costs or sacrifices. After carrying out a strategy that is assisted by cost, the result is a reward. Keywords: Selling Strategy, Social Exchange, Morning Market of Arengka